Pengaruh Pembiayaan Bagi Hasil Mudharabah dan Musyarakah terhadap Profitabilitas (Pada Bank Panin Dubai Syariah Periode Maret 2019 - September 2020) - Siti Humayah; Wirman Wirman (Universitas Muhammadiyah Surabaya, 2022)
This study aims to find out the influence of Mudharabah and Musyarakah on the profitability of Sharia banks projected with Return on Assets (ROA). The data used is derived from the quarterly financial statements of Bank Panin Dubai Syariah for the period March 2019-September 2020. The research method used in this study is to use multiple linear, regression, and test the classical assumption of normality test, multikoloniaritas, heteroksidasitas, and autokorolation, while proving the hypothesis of determination R2, F statistical test, and the test T statistic. The results showed that mudharabah financing variable (X1) is negative value and has no influence on ROA (Y). While musyarakah financing variable (X2) is positive value and has no influence on ROA (Y).